The impacts of violence against women on the mental health of victims: Integrative literature review (Research, Society and Development, 2024)
Objective: To identify scientific productions on the impacts of violence against women on the mental health of victims. Methods: An integrative review aimed at answering the guiding question: What are the impacts of violence on the mental health of women described in the literature? National articles published in Portuguese, English, or Spanish, available in full text, between the years 2013 and 2023, with the descriptors violence against women and mental health, indexed in the MEDLINE, LILACS, and SCIELO databases were included. Results: Six scientific productions were found. The analysis of the studies revealed that violence against women has diverse and severe impacts on mental health, including associations with the use of sleep-inducing medications and suicidal ideation, as well as a strong link with common mental disorders such as depression and anxiety. These effects persist even during pregnancy, when psychological violence increases the risk of developing mental disorders. Conclusion: The study provided an analysis of the impacts of violence against women on mental health, emphasizing the need for a coordinated approach among healthcare professionals, policymakers, and society to prevent and respond to this public health issue. The urgency of effective interventions, including systematic screenings, comprehensive intervention protocols, and interdisciplinary partnerships, was highlighted. Additionally, the importance of recognizing and addressing the various impacts of violence by investing in professional training and creating a safe and supportive environment for all women was underscored.